2021
DOI: 10.3389/fpsyg.2020.589554
|View full text |Cite
|
Sign up to set email alerts
|

Sports and Functional Training Improve a Subset of Obesity-Related Health Parameters in Adolescents: A Randomized Controlled Trial

Abstract: To investigate the effects of two different modes of physical activity on body composition, physical fitness, cardiometabolic risk, and psychological responses in female adolescents participating in a multi-disciplinary program. The 12-week randomized intervention included 25-adolescents with overweight divided into two groups: sports practice-SPG and functional training-FTG. The SPG intervention was divided into three sports: basketball, handball, and futsal. SPG participants performed one sport 3-times/week,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…Besides that, it was essential to emphasize that low levels of cardiorespiratory fitness could impact obese adolescents ( Alemayehu et al, 2018 ; Salvadego et al, 2018 ). Thus, public policies to promote physical activity, healthy nutrition and safe mental health are indispensable in the early stages of life ( Branco et al, 2019 ; Branco et al, 2020 ; Branco et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, it was essential to emphasize that low levels of cardiorespiratory fitness could impact obese adolescents ( Alemayehu et al, 2018 ; Salvadego et al, 2018 ). Thus, public policies to promote physical activity, healthy nutrition and safe mental health are indispensable in the early stages of life ( Branco et al, 2019 ; Branco et al, 2020 ; Branco et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, each type of exercise has different physiological effects (Woolf-May et al, 2000 ; Finucane et al, 2010 ; Koh et al, 2018 ; Chiang et al, 2019 ), and even for the same exercise, there are different effects at different intensities (Asikainen et al, 2003 ; Cho et al, 2018 ). Besides, frequency and duration are also important factors (Woolf-May et al, 1999 ), so we calculated the intensity, frequency, and duration of PA based on the preferences of the population, as discussed in the previous study (Branco et al, 2021 ). Despite the fact that football accounts for a 51% share of the global sports market (Yam et al, 2020 ), the most popular PA forms reported were “Brisk walking” and “Running,” followed by “Resistance Training” and “Square Dance.” Furthermore, ~60% of individuals experienced low-intensity PA, and just 7.6% reported high intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant association of BMI with depression among our study participants, a similar study conducted in Sweden reported that after controlling for Nordic ancestry, neuropsychiatric diseases, family history of anxiety/depression, and socioeconomic level, obesity remained a significant risk factor for anxiety and depression in children and adolescents of school-going age. When compared to females in the general school population, obese girls had a 43% higher risk of anxiety and depression [ 21 ].…”
Section: Discussionmentioning
confidence: 99%